Extremely High Glass Transition Temperature Hydrocarbon Polymers Prepared through Cationic Cyclization of Highly 3, 4‐Regulated Poly(Phenyl‐1, 3‐Butadiene). Issue 20 (7th August 2018) - Cai, Yang; Lu, Jianmin; Zuo, Danlin; Li, Shihui; Cui, Dongmei; Han, Bingyong; Yang, Wantai
Abstract: A simple approach to synthesize extremely high glass transition temperature (Tg > 300 °C) hydrocarbon polymers that introduces bridged cyclic backbone and bulky pendant group simultaneously is reported. This method uses highly 3, 4‐regulated poly(phenyl‐1, 3‐butadiene) as a prepolymer for cationic cyclization postmodification. The Tg of cyclized highly 3, 4‐regulated (94.0%) poly(1‐phenyl‐1, 3‐butadiene) (P(1‐PB)) can reach 304 °C. To further restrict the movement of bridged cyclic backbone by changing the position of the pendant substituent group, highly 3, 4‐regulated (96.2%) poly(2‐phenyl‐1, 3‐butadiene) (P(2‐PB)) is used as the prepolymer. The Tg of its cyclized product reaches 325 °C, and this value is the highest ever reported among all hydrocarbon polymers. The results indicate that the regularity of poly(phenyl‐1, 3‐butadiene) and the pendant substituent group are crucial factors when synthesizing high‐temperature hydrocarbon polymers through this approach. Abstract : A simple approach for the synthesis of extremely high glass transition temperature (Tg) hydrocarbon polymers via cationic cyclization of diene polymers is reported. The Tg of cyclized 3, 4‐regulated (94.0%) poly(1‐phenyl‐1, 3‐butadiene) reaches 304 °C, and that of cyclized 3, 4‐regulated (96.2%) poly(2‐phenyl‐1, 3‐butadiene) reaches 325 °C. The combination of high regularity of prepolymer and aromatic bulky pendant group is the key for this approach.